2010
DOI: 10.1111/j.1751-7141.2009.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Glutamyl Transferase: A Novel Cardiovascular Risk BioMarker

Abstract: Gamma‐glutamyl transferase (GGT) is a second‐generation enzymatic liver function test available for several decades, initially used as a sensitive indicator of alcohol ingestion, hepatic inflammation, fatty liver disease, and hepatitis. Longitudinal and cross‐sectional investigational studies since 1990 have associated GGT with an increase in all‐cause mortality, as well as chronic heart disease events such as congestive heart failure and components of the metabolic syndrome (abnormal body mass index and level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
138
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 29 publications
8
138
2
3
Order By: Relevance
“…24,25 GGT assaying is a liver function test that is used as a sensitive indicator of alcohol consumption and hepatobiliary dysfunction. 26 GGT is found not only in the liver, but also in the kidneys and vascular epithelium, as well as in the extracellular fluid, where it is attached to albumin carrier molecules and lipoproteins. 27 Previous studies have shown that increased GGT levels are associated with decreased oxygen levels and increased levels of inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 GGT assaying is a liver function test that is used as a sensitive indicator of alcohol consumption and hepatobiliary dysfunction. 26 GGT is found not only in the liver, but also in the kidneys and vascular epithelium, as well as in the extracellular fluid, where it is attached to albumin carrier molecules and lipoproteins. 27 Previous studies have shown that increased GGT levels are associated with decreased oxygen levels and increased levels of inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Виявлено такі нові фактори ризи-ку: С-реактивний білок (СРБ), гомоцистеїн, ліпо-протеїн (а) [11], мікроальбумінурія (МАУ) [28], се-чова кислота [7,10,25,27] [34].…”
Section: фактори ризику і предиктори виникнення ішемічної хвороби серunclassified
“…Окрім цього, вона позитивно корелює з ризиком серцево-судинних подій і підви-щеним ризиком загальної смертності. ҐҐТП можна розглядати як маркер оксидативного стресу, який має стосунок до метаболізму ґлутатіону, і, можливо, як проатероґенний маркер, позаяк він опосередкова-но стосується каскаду окиснення ЛПНГ [28]. Дове-дено, що жінки з підвищеним рівнем ҐҐТП мали ви-щий рівень коронарного кальцію (> 100,0) і більшу поширеність МС.…”
Section: фактори ризику і предиктори виникнення ішемічної хвороби серunclassified
“…I agree with him that uric acid and gamma-glutamyl transferase values have been examined in previous studies of the extent, severity, and complexity of coronary artery disease [2,3]. Because of this, we first aimed to investigate the association between the monocyte/HDL-C ratio and SYNTAX score in patients with stable coronary artery disease.…”
mentioning
confidence: 91%